Systemic immune-inflammation index and bone mineral density in postmenopausal women: A cross-sectional study of the national health and nutrition examination survey (NHANES) 2007-2018 - Tang, Yuchen; Peng, Bo; Liu, Jinmin; Liu, Zhongcheng; Xia, Yayi; Geng, Bin (Frontiers in Immunology, 2022)
Background: This study aimed to investigate the association between the SII and BMD and to determine the association between the SII and the risk of osteopenia/osteoporosis among postmenopausal women aged ≥50 years. Methods: Postmenopausal women aged ≥50 years from the National Health and Nutrition Examination Survey were included. BMD testing was performed using dual-energy X-ray absorptiometry. The SII was calculated based on lymphocyte (LC), neutrophil (NC), and platelet (PC) counts. Moreover, the associations of BMD with SII and other inflammatory markers, including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), the product of platelet count and neutrophil count (PPN), PC, NC, and LC, were assessed using a multivariable weighted linear regression model. Additionally, the associations of low BMD/osteoporosis with SII and other inflammatory markers were assessed using multivariable weighted logistic regression. Results: Finally, a total of 893 postmenopausal women with a weighted mean age of 60.90±0.26 years were included finally. This study found that SII was negatively associated with total femur BMD and femoral neck BMD, and postmenopausal women in a higher SII quarter group showed low lumbar spine BMD than the lowest SII quarter group when SII was converted from a continuous variable to a categorical variable. Moreover, increased SII was associated with an increased risk of low BMD and osteoporosis. In addition, this study observed that other inflammatory markers, especially NLR and PPN, were negatively associated with BMD and positively associated with the risk of osteoporosis. Finally, the subgroup analysis showed that the associations between BMD and inflammatory markers were pronounced in postmenopausal women aged ≥65 years or those with normal BMI (<25 kg/m2). Conclusion: SII may be a valuable and convenient inflammatory marker that could be applied to predict the risk of low BMD or osteoporosis among postmenopausal women aged ≥50. Moreover, postmenopausal women with a high level of SII or other inflammatory markers, such as NLR and PPN, should be aware of the potential risk of osteoporosis. However, given the inherent limitations of the present study, additional large-scale studies are required to investigate the role of SII in osteoporosis further.